A powder-metallurgy-based fabrication route towards achieving high tensile strength with ultra-high ductility in high-entropy alloy. (1st January 2021) - Asghari-Rad, Peyman; Sathiyamoorthi, Praveen; Nguyen, Nhung Thi-Cam; Zargaran, Alireza; Kim, Taek Soo; Kim, Hyoung Seop
Abstract: The strength-ductility trade-off dilemma is perennially problematic in the materials science community. In particular, the attainability of high tensile strength and large elongation is ambitious in alloys fabricated by powder metallurgy. Here, we demonstrate a powder-metallurgy-based fabrication route to achieve a high synergy of tensile strength and ductility through cold-consolidation of CoCrFeMnNi high-entropy alloy powder using high-pressure torsion followed by annealing. This approach has resulted in an exceptional synergy of high yield strength of 754 MPa with an ultra-high tensile elongation of 58%% which has never been achieved in alloys fabricated by powder metallurgy routes. Additionally, the microstructure can be tuned by annealing treatment to achieve a range of strength and ductility that are highly sought after in industries for a specific application. The present fabrication route can be applied for fabrication of high-entropy alloy-matrix composites using alloys, metals, and ceramic powders to achieve controllable microstructure and eminent tensile properties. Graphical abstract: Image, graphical abstract